The Interstitial Lymphatic Peritoneal Mesothelium Axis in Portal Hypertensive Ascites: When in Danger, Go Back to the Sea - M. A. Aller; I. Prieto; S. Argudo; F. de Vicente; L. Santamaría; M. P. de Miguel; J. L. Arias; J. Arias (International Journal of Inflammation)
Portal hypertension induces a splanchnic and systemic low-grade inflammatory response that could induce the expression of three phenotypes, named ischemia-reperfusion, leukocytic, and angiogenic phenotypes.During the splanchnic expression of these phenotypes, interstitial edema, increased lymph flow, and lymphangiogenesis are produced in the gastrointestinal tract. Associated liver disease increases intestinal bacterial translocation, splanchnic lymph flow, and induces ascites and hepatorenal syndrome. Extrahepatic cholestasis in the rat allows to study the worsening of the portal hypertensive syndrome when associated with chronic liver disease. The splanchnic interstitium, the mesenteric lymphatics, and the peritoneal mesothelium seem to create an inflammatory pathway that could have a key pathophysiological relevance in the production of the portal hypertension syndrome complications. The hypothetical comparison between the ascitic and the amniotic fluids allows for translational investigation. From a phylogenetic point of view, the ancestral mechanisms for amniotic fluid production were essential for animal survival out of the aquatic environment. However, their hypothetical appearance in the cirrhotic patient is considered pathological since ultimately they lead to ascites development. But, the adult human being would take advantage of the potential beneficial effects of this “amniotic-like fluid” to manage the interstitial fluids without adverse effects when chronic liver disease aggravates.